Автори українських мандрівних нарисів 1920 – 1930-х років як агенти і шпигуни - Васьків, М.С. (Слово і Час, 2019)
У статті йдеться про залучення в 1920 – 1930-ті роки українських авторів мандрівних нарисів про
закордонне буття до розвідницько-шпигунської діяльності в різних формах. Це було виконання
побіжних завдань поруч із відтворенням побаченого, на що вказують різноманітні “сліди” в
нарисових текстах книжок С. Голованівського, О. Досвітнього, К. Котка, Л. Недолі, В. Поліщука
та ін. У цьому переконують численні обмовки, недомовки, повідомлення про дивні маршрути
мандрів, неодноразові зустрічі з радянськими консульськими й посольськими працівниками,
політичними емігрантами й нелегалами, митцями лівого спрямування. The article deals with the engagement of the Ukrainian authors of travel essays about foreign life to
the intelligence and spy activities in diff erent forms, usually for performing the special tasks alongside
with observation and making literary notes. Various textual ‘footprints’ in their travel writings prove this
fact. In two interwar decades Ukrainian travel writings had a period of rise and rapid development;
they were generously financed by publishing houses, editorial boards of the magazines, different state
institutions and labor unions. Numerous books by amateur and experienced professional writers,
predominantly about their trips around Ukrainian and other Soviet lands, were published in large
numbers. Very often the travelers were professional military men, secret agents or followed out the
instructions of the special service, openly recognizing it in their books.
Not so many, but still a lot of travel writings described what had been seen, heard and read abroad.
Crossing the border of the USSR required essential expenses in foreign currency and special
permissions; therefore only selected representatives of literature could visit European and Asian
countries. This fact makes one suspect them of cooperation with diff erent intelligence institutions.
The textual analysis of the books written by S. Holovanivskyi, O. Dosvitnii, K. Kotko, L. Nedolia, V.
Polishchuk and others proves that these suspicions are well-grounded. It is evidenced by numerous
slips, omissions, reports on rather strange travel routes, repeated meetings abroad with Soviet
consular and embassy employees, political emigrants, illegal immigrants and left-wing artists. It is
obvious that the essayists were the transmitters of secret information in oral form addressed both
abroad and backwards, so that it could not be found by any customs officers or counterintelligence
agents. It seems that such a secret mission influenced the texts of travel writings, intensifying their
anti-Western, ‘anti-capitalist’ orientation and class bias.